Path-tracking errors for active trailer steering off-highway: a simulation study. (29th July 2019) - Miao, Qiheng; Cebon, David
This paper discusses the tracking performance of a path-following steering system when operating off-highway. Simulation studies were conducted on three types of vehicle models: tractor-semitrailer, B-double and A-triple. The vehicles were simulated for a straight-line and a 450 roundabout with various road camber, grade and adhesions. Results indicated that the path-following steering system was unable to provide good tracking performance under those conditions due to longitudinal and lateral wheel slip interfering with its estimation of trailer location and orientation.